Róznice w technice wioslowania na czwórce podwójnej - Jaszczak, M. (2003)
The inverse dynamics problem was solved for rowing at different stroke rates on the Concept II model C ergometer. It has been attempted to define the technique differences between the members of a single crew during rowing at increasing stroke rates and between crews of different performance levels. The most significant technique differences have been found on the one hand between the fourth rower and the others and, on the other hand, between the international level, less technically diversified and the national level crews. Rowing is a cyclic sport. It consists in propelling the boat to the velocity that makes it possible to cover a distance of 2000 m in the shortest time possible. The most beneficial velocity is one that could be maintained during the whole race. In the multi-person boat, one of the factors vital to sport success is the harmony between rowers, i.e. rowing at the same rhythm and using the same technique. Thus the purpose of this study was to define the technique differences between members of one crew during rowing at increasing stroke rate and between crews of different performance levels. Rowing technique was described by the time histories of the main muscle group moments [8]. The rowers of two quadruple sculls participated in the study. The first one had competed in World Championships Finals and the second one in Polish Championships Finals. The first stage of the research consisted in measuring the force on the ergometer grip and the main joints' displacements during the ten maximal strokes on the Concept II model C ergometer at stroke rates of 32 s/min, 36 s/min and 40 s/min. In the second stage, a 3D biomechanical model was built using the DADS (CADS Inc., USA) software package and the inverse dynamics problem was solved to obtain the time histories of the main muscle group moments. Technique differences between the members of one crew were studied by comparing computed time histories using the unfit coefficient (1 - r2, r - Pearson's coefficient). Subsequently, the differences between international and national level crews were tested at increasing stroke rate, using ANOVA. Results showed differences in the ankle and the hip joint during rowing at 36 s/min between the fourth rower sitting closest to the bow of the boat and the other national level rowers on quadruple sculls. The second and the fourth member of the international level crew showed, apart from similar differences in the ankle and hip joints, also a difference in the knee joint, but at 32 s/min. The greatest technique diversity was observed at the studied stroke rates in the elbow joint (between all rowers). ANOVA has revealed that the average value of the technique correlation coefficient within the international level crew increased along with stroke rate (although in the elbow joint it was lower than in the other joints), which implied a decline in technique diversity. For the national level quadruple sculls the average value of the correlation coefficient of the computed time histories was almost the same at the extreme stroke rates, but at the middle stroke rate it was clearly lower. Interaction between crews of different levels showed the greatest technique diversity at 36 s/min in all studied joints except the elbow joint, and the average value of the correlation coefficient of the computed time histories for international level rowers was higher at stroke rates between 36 s/min and 40 s/min than for the national level rowers. Regarding the elbow joints, national level rowers had a higher average value of the technique correlation coefficient and the technique diversity was the highest at 32 s/min. Sport technique differences between the fourth rower and the others show that his technique is different (bad?). This fact could be one of the reasons explaining poorer sport results. The rower sitting closest to the bow should have a very good technique, because his behaviour determines the boat balance. In a multi-person boat his task is especially difficult, because he is subject to more distinct wobbling than the others. One can suppose that the lower technique diversity of the international level crew compared with the national level crew makes it possible for them to achieve better results, all the more so as these discrepancies were the highest during rowing at 36 s/min, which is the average racing stroke rate of quadruple sculls. The elbow joint turned out to be the joint with the highest technique diversity regardless of both the crew's level and the stroke rate.